MicroRNAs that affect prostate cancer: emphasis on prostate cancer in African Americans. (October 2013) - Jones, J; Grizzle, W; Wang, H; Yates, C
Abstract Although concerted efforts have been directed toward eradicating health disparities in the United States, the disease and mortality rates for African American men still are among the highest in the world. We focus here on the role of microRNAs (miRNAs) in the signaling pathways of androgen receptors and growth factors that promote the progression of prostate cancer to more aggressive disease. We explore also how differential expression of miRNAs contributes to aggressive prostate cancer including that of African Americans.